Battery and preparation method thereof, energy storage device and power system

By providing a diaphragm coating on the separator substrate of the negative electrode sodium metal battery and a negative electrode coating on the negative electrode current collector, it is made to bond with the diaphragm coating to form an integrated structure, which solves the problems of low battery processing efficiency and reduced flatness of the current collector, extends the cycle life of the battery and reduces dendrites.

CN119786706APending Publication Date: 2025-04-08XIAMEN HITHIUM ENERGY STORAGE TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411854191.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

During the manufacturing process, the negative electrode-free sodium metal battery has weak current collector strength and easy wrinkle, resulting in a decrease in battery processing efficiency and a decrease in current collector flatness, which affects the sodium metal nucleation and cycle life.

Method used

A diaphragm coating is provided on both sides of the diaphragm substrate that exceeds the positive electrode sheet in the width direction, and a negative electrode coating is provided on a part of the surface of the negative electrode current collector close to the diaphragm, so that the negative electrode coating is bonded to the diaphragm coating to form an integrated structure to form a space to jointly form a space to accommodate the active ions released by the positive electrode sheet.

Benefits of technology

It effectively avoids internal stress accumulation of the battery cell caused by changes in the volume of active metal on the negative electrode side, improves the strength of the negative electrode sheet, extends the cycle life of the battery and reduces dendrites.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119786706A_ABST
    Figure CN119786706A_ABST
Patent Text Reader

Abstract

The present application belongs to the field of energy storage, and specifically discloses a battery and a preparation method thereof, an energy storage device and an electricity consumption system, wherein the battery comprises a positive electrode sheet and a diaphragm-negative electrode assembly, the diaphragm-negative electrode assembly comprises a negative electrode sheet and a diaphragm, the diaphragm comprises a diaphragm substrate and a diaphragm coating, the diaphragm coating is arranged on a partial surface of the diaphragm substrate close to the negative electrode sheet, and the diaphragm coating is arranged on both sides of the diaphragm substrate that exceed the positive electrode sheet in the width direction; the negative electrode sheet comprises a negative electrode collector and a negative electrode coating, the negative electrode coating is arranged on at least a partial surface of the negative electrode collector close to the diaphragm, and the two ends of the negative electrode coating in the width direction are respectively bonded to at least a portion of the diaphragm coating on both sides of the diaphragm substrate in the width direction to form a bonding area, the bonding area is formed by hot pressing after laminating the negative electrode sheet and the diaphragm, the negative electrode coating, the diaphragm coating on both sides and the diaphragm substrate jointly form a space, and the space is used to accommodate the metal formed by the active ions released by the positive electrode sheet and deposited on the negative electrode side.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the field of energy storage, and specifically relates to a battery and a preparation method thereof, an energy storage device and an electricity consumption system. Background Art

[0002] In order to further obtain higher cell energy density, a "negative electrode-free" sodium metal battery was developed by first removing sodium from the positive electrode active material and depositing it in situ onto the negative electrode current collector. Compared with the thickness of the negative electrode of lithium-ion / sodium-ion batteries, the thickness of the negative electrode side of the negative electrode-free battery is significantly reduced (its thickness is generally less than 15μm) because the negative electrode side does not include the negative electrode active material layer during battery assembly. In the actual manufacturing process of the negative electrode-free battery (including but not limited to the stacking / winding negative electrode transmission, traction, stretching, and absorption process), due to the weak strength and easy wrinkling of the thin current collector, it is easy to cause the battery processing efficiency to decrease and the current collector flatness to decrease, thereby affecting the nucleation of sodium metal on the negative electrode side, and it is also easy to cause problems such as cycle life attenuation and even the generation of dendrites.

[0003] In addition, metal deposition or detachment on the negative electrode side will cause huge volume change problems, easily causing serious deformation of the electrode interface, thus significantly affecting the electrical performance of the battery cell. Summary of the invention

[0004] The present application aims to solve at least one of the technical problems in the related art to a certain extent. To this end, one purpose of the present application is to provide a battery and a method for preparing the same, an energy storage device and an electricity system. The present application can form a space for accommodating the metal formed by the deposition of active ions released by the positive electrode sheet on the negative electrode side by arranging a diaphragm coating on both sides of the diaphragm substrate in the width direction beyond the positive electrode sheet, thereby effectively avoiding the accumulation of stress inside the battery cell caused by the volume change of the active metal on the negative electrode side, and further effectively avoiding the failure of the battery cell's cycle performance or the failure of the battery cell's structural parts. At the same time, the diaphragm and the negative electrode sheet can also be effectively formed into an integrated structure to improve the strength of the negative electrode sheet.

[0005] In a first aspect, the present application provides a battery. According to an embodiment of the present application, the battery includes: a positive electrode sheet and a diaphragm-negative electrode assembly, the diaphragm-negative electrode assembly includes a negative electrode sheet and a diaphragm, the diaphragm is arranged between the positive electrode sheet and the negative electrode sheet, the diaphragm includes a diaphragm substrate and a diaphragm coating, the diaphragm coating is arranged on a portion of the surface of the diaphragm substrate close to the negative electrode sheet, and the diaphragm coating is arranged on both sides of the diaphragm substrate in the width direction beyond the positive electrode sheet;

[0006] The negative electrode sheet includes a negative electrode current collector and a negative electrode coating, wherein the negative electrode coating is arranged on at least a portion of the surface of the negative electrode current collector close to the diaphragm, and the two ends of the negative electrode coating along the width direction are respectively bonded to at least a portion of the diaphragm coating on both sides of the diaphragm substrate along the width direction to form a bonding area, and the bonding area is formed by hot pressing the negative electrode sheet and the diaphragm after stacking, and the negative electrode coating, the diaphragm coating on both sides and the diaphragm substrate together form a space, and the space is used to accommodate the metal formed by the active ions released by the positive electrode sheet deposited on the negative electrode side.

[0007] According to the battery of the above-mentioned embodiment of the present application, by respectively arranging a diaphragm coating on both sides of the diaphragm substrate extending beyond the positive electrode sheet in the width direction, and at the same time arranging a negative electrode coating on at least a portion of the surface of the negative electrode current collector close to the diaphragm, and the two ends of the negative electrode coating in the width direction are respectively at least partially bonded to the diaphragm coating on both sides of the diaphragm substrate in the width direction, thereby, the negative electrode coating, the diaphragm coating on both sides and the diaphragm substrate can jointly form a space, and the space can be used to accommodate the metal (such as sodium metal) formed by the deposition of active ions released by the positive electrode sheet on the negative electrode side, thereby effectively avoiding the accumulation of stress inside the battery cell caused by the volume change of the active metal on the negative electrode side, and further effectively avoiding the failure of the cycle performance of the battery cell or the failure of the battery cell structural parts.

[0008] At the same time, the two ends of the negative electrode coating along the width direction are at least partially bonded to the diaphragm coating on both sides of the diaphragm substrate along the width direction, thereby effectively forming an integrated structure of the diaphragm and the negative electrode sheet, improving the strength of the negative electrode sheet, thereby effectively avoiding the problems of low battery processing efficiency and reduced flatness of the collector caused by weak strength and easy wrinkling of the negative electrode sheet, problems affecting the nucleation of active metals on the negative electrode side, battery cycle life attenuation and dendrite generation, and being closer to actual equipment use and processing.

[0009] In addition, the battery according to the above embodiment of the present application may also have the following additional technical features:

[0010] In some embodiments of the present application, the positive electrode sheet includes a positive electrode current collector and a positive electrode active material, and the thickness H of the separator coating satisfies: H ≥ Q 正极 / (Q 活性金属 ·S 正极 )·(1±0.3), where Q 正极 represents the capacity released by the positive electrode active material, Q 活性金属 represents the volume gram capacity of the active metal of the positive electrode active material, S 正极 Represents the area of ​​the positive electrode sheet.

[0011] In some embodiments of the present application, the active metal of the positive electrode active material includes at least one of sodium and lithium.

[0012] In some embodiments of the present application, the diaphragm coating includes a ceramic coating and an organic glue layer, the ceramic coating is arranged on a portion of the surface of the diaphragm substrate close to the negative electrode sheet, and the ceramic coating is arranged on both sides of the diaphragm substrate beyond the positive electrode sheet in the width direction, and the organic glue layer is arranged on at least a portion of the surface of the ceramic coating away from the diaphragm substrate.

[0013] In some embodiments of the present application, the ceramic coating includes a ceramic material and a first aqueous binder, and the mass ratio of the ceramic material to the first aqueous binder is 9 / 1 to 7 / 3; and / or, the organic adhesive layer includes at least one of polyvinylidene fluoride-propylene fluoride and polymethyl methacrylate; and / or, the thickness of the organic adhesive layer is 0.5μm to 2μm, and the thickness of the ceramic coating is equal to the difference between the thickness H of the diaphragm coating and the thickness of the organic adhesive layer.

[0014] In some embodiments of the present application, the ceramic material includes at least one of alumina and boehmite; and / or the first aqueous binder includes at least one of styrene-butadiene rubber, carboxymethyl cellulose and polyacrylic acid.

[0015] In some embodiments of the present application, the width of the bonding between the negative electrode coating and the separator coating on one side is 1 mm to 10 mm.

[0016] In some embodiments of the present application, the negative electrode coating comprises a conductive carbon material and a second aqueous binder, the mass ratio of the conductive carbon material to the second aqueous binder is 9 / 1 to 7 / 3; and / or the thickness of the negative electrode coating is 1 μm to 2 μm.

[0017] In some embodiments of the present application, the conductive carbon material includes at least one of conductive carbon black, carbon nanotubes, graphene, and carbon fibers; and / or the second aqueous binder includes at least one of styrene-butadiene rubber, carboxymethyl cellulose, and polyacrylic acid.

[0018] The second aspect of the present application proposes a method for preparing a battery as described in the above embodiment. According to the embodiment of the present application, the preparation method comprises:

[0019] forming a negative electrode coating on at least a portion of the surface of the negative electrode current collector to obtain a negative electrode sheet;

[0020] Forming membrane coatings on both sides of the membrane substrate along the width direction to obtain a membrane;

[0021] The negative electrode sheet and the separator are stacked and hot pressed so that both ends of the negative electrode coating along the width direction are at least partially bonded to the separator coating on both sides to form a separator-negative electrode assembly, and the negative electrode coating, the separator coating on both sides and the separator substrate together form a space.

[0022] According to the preparation method of the above embodiment of the present application, the two ends of the negative electrode coating along the width direction can be effectively bonded to the diaphragm coatings on both sides respectively, ensuring that the diaphragm and the negative electrode sheet form an integrated structure of the diaphragm-negative electrode assembly, and improving the strength of the negative electrode sheet, thereby effectively avoiding the problems of low battery processing efficiency and reduced flatness of the current collector caused by weak strength and easy wrinkling of the negative electrode sheet, problems affecting the nucleation of active metals on the negative electrode side, battery cycle life attenuation and dendrite generation, and being closer to actual equipment use and processing. At the same time, the negative electrode coating, the diaphragm coatings on both sides and the diaphragm matrix formed by the method can form a space together, and the space can be used to accommodate the metal formed by the active ions released by the positive electrode sheet deposited on the negative electrode side, thereby effectively avoiding the internal stress accumulation of the battery cell caused by the volume change of the active metal on the negative electrode side, and further effectively avoiding the failure of the battery cell's cycle performance or the failure of the battery cell structure.

[0023] In addition, the preparation method according to the above embodiment of the present application may also have the following additional technical features:

[0024] In some embodiments of the present application, the temperature of the hot pressing is 60° C. to 80° C., the pressure of the hot pressing is 1 MPa to 2 MPa, and the time of the hot pressing is 1 min to 5 min.

[0025] The third aspect of the present application proposes an energy storage device. According to an embodiment of the present application, the above energy storage device includes a battery of the above embodiment or a battery obtained by the preparation method of the above embodiment. As a result, the energy storage device has excellent cycle performance and excellent cycle life, and the battery cell structure of the energy storage device is stable. It should be noted that the above-described features and advantages for the battery are also applicable to the energy storage device and will not be repeated here.

[0026] The fourth aspect of the present application proposes an electric power system. According to an embodiment of the present application, the electric power system includes: electric equipment, and an energy storage device as in the above embodiment, and the energy storage device supplies power to the electric equipment. As a result, the electric power system has excellent cycle performance and excellent cycle life. It should be noted that the above-described features and advantages for the battery are also applicable to the electric power system and will not be repeated here.

[0027] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through the practice of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] The above and / or additional aspects and advantages of the present application will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:

[0029] Figure 1 This is a schematic diagram of the structure of the battery of some embodiments of the present application.

[0030] Reference numerals:

[0031] 100 - positive electrode sheet, 200 - diaphragm, 210 - diaphragm substrate, 220 - diaphragm coating, 221 - ceramic coating, 222 - organic glue layer, 300 - negative electrode sheet, 310 - negative electrode current collector, 320 - negative electrode coating. DETAILED DESCRIPTION

[0032] Embodiments of the present application are described in detail below, and examples of the embodiments are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present application, and should not be construed as limiting the present application.

[0033] The first aspect of the present application provides a battery. According to an embodiment of the present application, referring to the attached Figure 1 The battery comprises: a positive electrode sheet 100 and a diaphragm-negative electrode assembly, the diaphragm-negative electrode assembly comprises a negative electrode sheet 300 and a diaphragm 200, the diaphragm 200 is arranged between the positive electrode sheet 100 and the negative electrode sheet 300, the diaphragm 200 comprises a diaphragm substrate 210 and a diaphragm coating 220, the diaphragm coating 220 is arranged on a portion of the surface of the diaphragm substrate 210 close to the negative electrode sheet 300, and the diaphragm coating 220 is arranged on both sides of the diaphragm substrate 210 that exceed the positive electrode sheet 100 in the width direction, and the diaphragm coating 220 is not arranged in the area facing the positive electrode sheet 100; the negative electrode sheet 300 comprises A negative electrode current collector 310 and a negative electrode coating 320, wherein the negative electrode coating 320 is arranged on at least a portion of the surface of the negative electrode current collector 310 close to the diaphragm 200, and the two ends of the negative electrode coating 320 along the width direction are respectively bonded with at least a portion of the diaphragm coating 220 on both sides of the diaphragm substrate 210 along the width direction to form a bonding area, and the bonding area is formed by hot pressing after laminating the negative electrode sheet and the diaphragm, and the negative electrode coating 320, the diaphragm coating 220 on both sides and the diaphragm substrate 210 together form a space, and the space is used to accommodate the metal formed by the active ions released by the positive electrode sheet 100 and deposited on the negative electrode side.

[0034] It should be noted that in the attached Figure 1 , the Y direction represents the thickness direction, and the X direction represents the width direction.

[0035] In the present application, the negative electrode sheet and the diaphragm are first stacked and then hot pressed, so that the two ends of the negative electrode coating along the width direction are respectively bonded to at least part of the diaphragm coating on both sides of the diaphragm substrate along the width direction to form a bonding area, so that the negative electrode sheet and the diaphragm form an integrated diaphragm-negative electrode assembly. Then, the positive electrode sheet and the integrated diaphragm-negative electrode assembly are stacked in order, so that the diaphragm is between the positive and negative electrode sheets, and then a certain hot pressing and shaping is performed to form an overall winding core structure to obtain a bare cell, which is then loaded into a battery casing, dried and injected with electrolyte, and the above-mentioned battery is obtained after vacuum packaging, standing, forming, shaping and other processes.

[0036] The principle of the beneficial effect of the battery proposed in this application is described in detail below:

[0037] The present application arranges a diaphragm coating 220 on both sides of the diaphragm substrate 210 that extend beyond the positive electrode sheet 100 in the width direction, and arranges a negative electrode coating 320 on at least a portion of the surface of the negative electrode current collector 310 close to the diaphragm 200, and both ends of the negative electrode coating 320 in the width direction are at least partially bonded to the diaphragm coating 220 on both sides of the diaphragm substrate 210 in the width direction, thereby, the negative electrode coating 320, the diaphragm coating 220 on both sides and the diaphragm substrate 210 can jointly form a space, and the space can be used to accommodate the metal (such as sodium metal) formed by the active ions released by the positive electrode sheet 100 deposited on the negative electrode side, thereby effectively avoiding the internal stress accumulation of the battery cell caused by the volume change of the active metal on the negative electrode side, and further effectively avoiding the failure of the cycle performance of the battery cell or the failure of the battery cell structure.

[0038] At the same time, the two ends of the negative electrode coating 320 along the width direction are at least partially bonded to the diaphragm coating 220 on both sides of the diaphragm substrate 210 along the width direction to form a bonding area, and the bonding area is formed by hot pressing after stacking the negative electrode sheet and the diaphragm, thereby effectively forming the diaphragm 200 and the negative electrode sheet 300 into an integrated structure (i.e., diaphragm-negative electrode assembly), thereby improving the strength of the negative electrode sheet 300, thereby effectively avoiding the low battery processing efficiency and the decrease in the flatness of the collector caused by the weak strength and easy wrinkling of the negative electrode sheet 300, the problem of affecting the nucleation of the active metal on the negative electrode side, the battery cycle life attenuation and the problem of dendrite generation, and being closer to actual equipment use and processing.

[0039] According to some specific embodiments of the present application, the positive electrode sheet 100 includes a positive electrode current collector and a positive electrode active material, and the thickness H of the separator coating 220 satisfies: H ≥ Q 正极 / (Q 活性金属 ·S 正极 )·(1±0.3), where Q 正极 Indicates the capacity released by the positive electrode active material (in mAh), Q 活性金属Indicates the volumetric capacity of the active metal of the positive electrode active material (unit: mAh / m 3 ), S 正极 represents the area of ​​the positive electrode sheet 100 (unit: m 2 ), thus, limiting the thickness H of the diaphragm coating 220 within the above range can fully accommodate the active metal (such as sodium metal) released by the positive electrode sheet 100, thereby effectively avoiding the internal stress accumulation of the battery cell due to the volume change of the active metal on the negative electrode side, and further effectively avoiding the failure of the battery cell's cycle performance or the failure of the battery cell structure. Where (1±0.3) is the actual manufacturing tolerance range. Preferably, the thickness H of the diaphragm coating 220 satisfies: H=Q 正极 / (Q 活性金属 ·S 正极 )·(1±0.2).

[0040] According to some further specific embodiments of the present application, the active metal of the positive electrode active material includes at least one of sodium and lithium. When the above-mentioned battery is a sodium metal battery, the active metal of the positive electrode active material is sodium; when the above-mentioned battery is a lithium metal battery, the active metal of the positive electrode active material is lithium.

[0041] According to some other specific embodiments of the present application, the diaphragm coating 220 includes a ceramic coating and an organic glue layer, the ceramic coating is arranged on a portion of the surface of the diaphragm substrate 210 close to the negative electrode sheet 300, and the ceramic coating is arranged on both sides of the diaphragm substrate 210 that exceed the positive electrode sheet 100 in the width direction, and the organic glue layer is arranged on at least a portion of the surface of the ceramic coating away from the diaphragm substrate 210. Among them, the ceramic coating is not easy to deform and is used to support the thickness of the diaphragm coating 220. The organic glue layer is used to bond the diaphragm coating 220 and the negative electrode coating 320 together, so that the diaphragm 200 and the negative electrode sheet 300 form an integrated structure, which improves the strength of the negative electrode sheet 300.

[0042] According to some other specific embodiments of the present application, the ceramic coating includes a ceramic material and a first aqueous binder, and the mass ratio of the ceramic material to the first aqueous binder is 9 / 1 to 7 / 3 (for example, it can be 9 / 1, 8 / 2, 7 / 3, etc.). Thus, it can be ensured that the ceramic coating has the characteristic of not being easy to deform, thereby ensuring the thickness of the diaphragm coating 220, and can also ensure that the ceramic coating has certain bonding properties, thereby effectively forming the ceramic coating on the diaphragm substrate 210.

[0043] According to some other specific embodiments of the present application, the organic glue layer includes at least one of polyvinylidene fluoride-propylene fluoride (PVDF-HFP) and polymethyl methacrylate (PMMA). The organic glue layer formed thereby can further effectively bond the ceramic coating and the negative electrode coating 320 together, thereby forming an integrated structure with the separator 200 and the negative electrode sheet 300, thereby improving the strength of the negative electrode sheet 300.

[0044] According to some other specific embodiments of the present application, the thickness of the organic glue layer is 0.5μm to 2μm (for example, it can be 0.5μm, 1μm, 1.5μm, 2μm, etc.), thereby further ensuring that the organic glue layer bonds the ceramic coating and the negative electrode coating 320 together, thereby forming an integrated structure with the diaphragm 200 and the negative electrode sheet 300, further improving the strength of the negative electrode sheet 300.

[0045] According to some other specific embodiments of the present application, the thickness of the ceramic coating is equal to the difference between the thickness H of the diaphragm coating 220 and the thickness of the organic glue layer. The ceramic coating is not easily deformed and is used to support the thickness of the diaphragm coating 220, thereby ensuring that the space formed by the diaphragm coating 220 can fully accommodate the active metal (such as sodium metal) released by the positive electrode sheet 100.

[0046] In the embodiments of the present application, the specific types of the above-mentioned ceramic materials are not particularly limited, and those skilled in the art may select them according to actual needs. As some preferred embodiments, the ceramic material includes at least one of alumina and boehmite.

[0047] In the embodiments of the present application, the specific type of the above-mentioned first aqueous binder is not particularly limited, and those skilled in the art can select it according to actual needs. As some preferred embodiments, the first aqueous binder includes at least one of styrene-butadiene rubber (SBR), carboxymethyl cellulose (CMC) and polyacrylic acid (PAA).

[0048] According to some specific embodiments of the present application, the width of the negative electrode coating 320 and the diaphragm coating 220 on one side is 1 mm to 10 mm (for example, 1 mm, 2 mm, 4 mm, 6 mm, 8 mm, 10 mm, etc.), that is, the width of the unilateral bonding area is 1 mm to 10 mm. By limiting the width of the negative electrode coating 320 and the diaphragm coating 220 on one side (the width of the unilateral bonding area) to the above range, it can ensure that the negative electrode coating 320 and the diaphragm coating 220 are effectively bonded, thereby ensuring that the diaphragm 200 and the negative electrode sheet 300 form an integrated structure, and it can also ensure that the space formed by the negative electrode coating 320, the diaphragm coating 220 on both sides and the diaphragm substrate 210 is large enough to accommodate the metal formed by the active ions released by the positive electrode sheet deposited on the negative electrode side. Preferably, it is 5 mm to 8 mm.

[0049] According to some other specific embodiments of the present application, the negative electrode coating includes a conductive carbon material and a second aqueous binder, and the mass ratio of the conductive carbon material to the second aqueous binder is 9 / 1 to 7 / 3 (for example, it can be 9 / 1, 8 / 2, 7 / 3, etc.). This can further ensure that the nucleation energy of metallic sodium on the surface of the negative electrode current collector is reduced, and can further ensure that the negative electrode coating and the diaphragm coating are effectively bonded.

[0050] According to some other specific embodiments of the present application, the thickness of the negative electrode coating is 1 μm to 2 μm (for example, it can be 1 μm, 1.2 μm, 1.4 μm, 1.6 μm, 1.8 μm, 2 μm, etc.), thereby further ensuring that the nucleation energy of metallic sodium on the surface of the negative electrode current collector is reduced, and further ensuring that the negative electrode coating and the separator coating are effectively bonded.

[0051] In the embodiments of the present application, the specific types of the above-mentioned conductive carbon materials are not particularly limited, and those skilled in the art can select them according to actual needs. As some preferred embodiments, the conductive carbon materials include at least one of conductive carbon black (SP), carbon nanotubes (CNT), graphene, and carbon fibers.

[0052] In the embodiments of the present application, the specific type of the second aqueous binder is not particularly limited, and those skilled in the art may select it according to actual needs. As some preferred embodiments, the second aqueous binder includes at least one of styrene-butadiene rubber (SBR), carboxymethyl cellulose (CMC) and polyacrylic acid (PAA).

[0053] In the embodiments of the present application, the specific type of the above-mentioned diaphragm matrix is ​​not particularly limited, and those skilled in the art can select it according to actual needs. As some preferred embodiments, the diaphragm matrix includes at least one of a PP diaphragm and a PE diaphragm.

[0054] In the embodiments of the present application, the above-mentioned battery can be used for both a negative electrode-free sodium metal battery and a negative electrode-free lithium metal battery. The following is an example of a negative electrode-free sodium metal battery:

[0055] The negative electrode-free sodium metal battery comprises a positive electrode sheet, a separator, a negative electrode sheet and an electrolyte, wherein the separator is arranged between the positive electrode sheet and the negative electrode sheet. The characteristics of the separator and the negative electrode sheet are as described above and will not be repeated here.

[0056] The positive electrode sheet includes a positive electrode current collector and a positive electrode material layer formed on the positive electrode current collector, wherein the positive electrode material layer includes a positive electrode active material, a positive electrode binder and a positive electrode conductor.

[0057] For sodium metal batteries, the positive electrode active material may include, but is not limited to, one or more of transition metal oxides, polyanionic compounds, organic polymers, and Prussian blue materials. In sodium transition metal oxides, the transition metal may be at least one of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr, and Ce. The sodium transition metal oxide is, for example, Na x MO2, where M is one or more of Ti, V, Mn, Co, Ni, Fe, Cr and Cu, 0<x≤1, for example, Na[Ni 1 / 3 Fe 1 / 3Mn1 / 3 ]O2.

[0058] The polyanionic compound has sodium ions, transition metal ions and tetrahedral (YO4) n- A class of compounds of anion units, the transition metal can be at least one of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr and Ce; Y can be at least one of P, S and Si; n represents (YO4) n- valence state, for example Na3V2(PO4)3.

[0059] The above-mentioned Prussian blue compounds are sodium ions, transition metal ions and cyanide ions (CN - ) is a class of compounds whose general chemical formula can be expressed as Na x M1[M2(CN)6], wherein 0<x≤2, M1 and M2 are at least one of Ni, Cu, Fe, Mn, Co and Zn respectively.

[0060] The specific material of the positive electrode binder is not particularly limited. As some specific examples, the positive electrode binder may include but is not limited to one or more of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyacrylonitrile (PAN), and polyacrylic acid (PAA).

[0061] The specific material of the positive electrode conductive agent is not particularly limited. As some specific examples, the positive electrode conductive agent may include but is not limited to one or more of acetylene black, conductive carbon black, carbon nanotubes, carbon fibers, graphene, and the like.

[0062] In the embodiments of the present application, the specific material of the positive electrode current collector is not particularly limited. As some specific examples, the positive electrode current collector may include but is not limited to at least one of aluminum foil, carbon-coated aluminum foil, and stainless steel foil.

[0063] In the embodiments of the present application, the electrolyte includes electrolyte salt and organic solvent, wherein the specific types and compositions of the electrolyte salt and organic solvent are conventional choices in the battery field and can be selected according to actual needs.

[0064] In some embodiments, the electrolyte salt may include, but is not limited to, at least one of sodium hexafluorophosphate (NaPF6), sodium tetrafluoroborate (NaBF4), sodium perchlorate (NaClO4), sodium bis(trifluoromethanesulfonyl)imide (NaN(CF3SO2)2), sodium bis(fluorosulfonyl)imide (NaN(SO2F)2), sodium bis(oxalatoborate) (NaB(C2O4)2), and sodium difluorooxalatoborate (NaBF2C2O4).

[0065] In some embodiments, the organic solvent may include, but is not limited to, at least one of ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), fluoroethylene carbonate (FEC), diethylene glycol dimethyl ether (DEGDME), ethylene glycol dimethyl ether (DME), 1,3-dioxolane (DOL), and tetraethylene glycol dimethyl ether (TEGDME).

[0066] The second aspect of the present application proposes a method for preparing a battery of one or more embodiments. According to the embodiments of the present application, the above-mentioned preparation method includes: forming a negative electrode coating on at least part of the surface of the negative electrode current collector to obtain a negative electrode sheet; forming a diaphragm coating on both sides of the diaphragm substrate along the width direction to obtain a diaphragm; stacking the negative electrode sheet and the diaphragm, and hot pressing, so that the two ends of the negative electrode coating along the width direction are respectively bonded to at least part of the diaphragm coating on both sides, and the negative electrode coating, the diaphragm coating on both sides and the diaphragm substrate together form a space.

[0067] Specifically, the above method includes:

[0068] S100: forming a negative electrode coating on at least a portion of the surface of the negative electrode current collector to obtain a negative electrode sheet;

[0069] In this step, the conductive carbon material, the second aqueous binder and the solvent are first mixed to form a negative electrode coating slurry, and then the negative electrode coating slurry is coated on at least a portion of the surface of the negative electrode collector and dried to form a negative electrode coating to obtain a negative electrode sheet.

[0070] S200: forming a diaphragm coating on both sides of the diaphragm substrate along the width direction to obtain a diaphragm;

[0071] In this step, the ceramic material, the first aqueous binder and the solvent are first mixed to form a ceramic coating slurry, and then the ceramic coating slurry is coated on the two side surfaces of the diaphragm substrate extending beyond the positive electrode sheet in the width direction, and dried to form a ceramic coating; then an organic glue layer is formed on at least a portion of the surface of the ceramic coating away from the diaphragm substrate to finally obtain a diaphragm.

[0072] S300: stacking the negative electrode sheet and the separator and hot pressing;

[0073] In this step, the negative electrode sheet and the separator are first stacked and then hot pressed so that the two ends of the negative electrode coating along the width direction are at least partially bonded to the separator coating on both sides to form a bonding area, so that the negative electrode sheet and the separator form an integrated structure of the separator-negative electrode assembly. At the same time, the negative electrode coating, the separator coating on both sides and the separator substrate together form a space.

[0074] According to some specific embodiments of the present application, the temperature of hot pressing is 60°C to 80°C (for example, 60°C, 65°C, 70°C, 75°C, 80°C, etc.), the pressure of hot pressing is 1MPa to 2MPa (for example, 1MPa, 1.2MPa, 1.4MPa, 1.6MPa, 1.8MPa, 2MPa, etc.), and the time of hot pressing is 1min to 5min (for example, 1min, 2min, 3min, 4min, 5min, etc.). Thus, it can be further ensured that the two ends of the negative electrode coating along the width direction are effectively bonded to the diaphragm coating on both sides, ensuring that the diaphragm and the negative electrode sheet form an integrated structure.

[0075] According to the method of the embodiment of the present application, the two ends of the negative electrode coating along the width direction can be effectively bonded to the diaphragm coatings on both sides respectively, ensuring that the diaphragm and the negative electrode sheet form an integrated structure of the diaphragm-negative electrode assembly, and improving the strength of the negative electrode sheet, thereby effectively avoiding the problems of low battery processing efficiency and reduced flatness of the current collector caused by weak strength and easy wrinkling of the negative electrode sheet, problems affecting the nucleation of active metals on the negative electrode side, battery cycle life attenuation and dendrite generation, and being closer to actual equipment use and processing. At the same time, the negative electrode coating, the diaphragm coatings on both sides and the diaphragm matrix formed by the method can form a space together, and the space can be used to accommodate the metal formed by the deposition of active ions released by the positive electrode sheet on the negative electrode side, thereby effectively avoiding the internal stress accumulation of the battery cell caused by the volume change of the active metal on the negative electrode side, and further effectively avoiding the failure of the battery cell's cycle performance or the failure of the battery cell structure.

[0076] The third aspect of the present application proposes an energy storage device. According to an embodiment of the present application, the above energy storage device includes a battery of the above embodiment or a battery obtained by the preparation method of the above embodiment. As a result, the energy storage device has excellent cycle performance and excellent cycle life, and the battery cell structure of the energy storage device is stable. It should be noted that the above-described features and advantages for the battery are also applicable to the energy storage device and will not be repeated here.

[0077] Specifically, the energy storage device of the present application may include but is not limited to a battery module, a battery pack, a battery system, etc. In addition, the energy storage device of the present application may also include at least one of an electric energy storage device for the power generation side of the power system, an electric energy storage device for the power distribution side of the power system (such as an electrochemical energy storage device), and an electric energy storage device for the user side of the power system.

[0078] The fourth aspect of the present application proposes an electric power system. According to an embodiment of the present application, the electric power system includes: electric equipment, and an energy storage device as in the above embodiment, and the energy storage device supplies power to the electric equipment. As a result, the electric power system has excellent cycle performance and excellent cycle life. It should be noted that the above-described features and advantages for the battery are also applicable to the electric power system and will not be repeated here.

[0079] The above-mentioned power consumption system may include but is not limited to mobile phones, tablet computers, laptop computers, desktop computers, smart bracelets, smart watches, e-readers, game consoles and other portable electronic devices. It may also include but is not limited to vehicles such as cars, trucks, cars, vans, motor vehicles, high-speed trains, electric vehicles, etc. In addition, it may also be various household appliances, such as but not limited to refrigerators, electric lights, air conditioners, etc.

[0080] The embodiments of the present application are described in detail below. It should be noted that the embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. In addition, unless otherwise explicitly stated, all reagents used in the following embodiments are commercially available or can be synthesized according to this article or known methods, and the reaction conditions not listed are also easily available to those skilled in the art.

[0081] Example 1

[0082] This embodiment provides a negative electrode-free sodium metal battery, and the preparation method thereof includes:

[0083] (1) Preparation of negative electrode sheet:

[0084] First, the conductive carbon black SP and the adhesive PAA are dispersed in the solvent water and mixed evenly to obtain the negative electrode coating slurry, the mass ratio of SP to the adhesive PAA is 8:2, and the negative electrode coating slurry is coated on the negative electrode current collector copper foil with a thickness of 8μm, and after drying, cold pressing, slitting, and cutting, it is ready for use. The thickness of the negative electrode coating is 1μm.

[0085] (2) Preparation of positive electrode sheet:

[0086] The positive electrode active material sodium iron phosphate pyrophosphate (NFPP), the conductive agent (Super-P), and the binder (PVDF) were mixed in a mass ratio of 96:2:2, the mixed powder was placed in a vacuum mixer, N-methylpyrrolidone (NMP) was added, and the mixture was stirred evenly to obtain a positive electrode slurry; the positive electrode slurry was evenly coated on the opposite sides of the positive electrode current collector aluminum foil, the coating width was 86 mm, the coating length was 52 mm, and the coating surface density was 163 g / m 2, the positive electrode current collector coated with the positive electrode slurry is transferred to an oven for drying, and then rolled and cut to obtain a positive electrode sheet. According to calculations, the theoretical capacity that the sodium iron phosphate pyrophosphate in the positive electrode sheet can release is 73mAh. The theoretical thickness H of the metal deposition on the negative electrode side is:

[0087] Among them, 1166*0.97 is the volume gram capacity of metallic sodium, and its unit is mAh / cm 3 .

[0088] (3) Preparation of diaphragm:

[0089] A polyethylene film with a thickness of 16 μm is used as the diaphragm matrix.

[0090] First, the ceramic material alumina, the aqueous binder SBR and the solvent are evenly mixed with the mass ratio of alumina to SBR being 8:2 to form a ceramic coating slurry, and then the ceramic coating slurry is coated on the two side surfaces of the diaphragm substrate exceeding the positive electrode sheet in the width direction, and dried to form a ceramic coating; then a PVDF-HFP organic adhesive layer is formed on the surface of the ceramic coating away from the diaphragm substrate, wherein the thickness of the PVDF-HFP organic adhesive layer is 1 μm, the thickness of the ceramic coating is 17.7 μm, and the total thickness of the diaphragm coating is 18.7 μm, and finally a diaphragm is obtained.

[0091] (4) Integrated design:

[0092] The negative electrode sheet and the separator are first stacked and then hot pressed at a temperature of 70°C, a pressure of 1 MPa and a time of 3 min, so that the two ends of the negative electrode coating along the width direction are respectively bonded to the separator coatings on both sides. The width of the negative electrode coating bonded to the separator coating on one side is 8 mm. The negative electrode coating, the separator coatings on both sides and the separator substrate together form a space, which is used to accommodate the sodium ions released by the sodium iron phosphate pyrophosphate in the positive electrode sheet and the metallic sodium deposited on the negative electrode side.

[0093] (5) Preparation of electrolyte:

[0094] The dried sodium hexafluorophosphate sodium salt was added into a mixed solvent of diethylene glycol dimethyl ether and tetraethylene glycol dimethyl ether to prepare an electrolyte with a concentration of 1 mol / L, and the volume ratio of diethylene glycol dimethyl ether to tetraethylene glycol dimethyl ether was 1:1.

[0095] (6) Preparation of sodium ion batteries:

[0096] The positive electrode sheet, integrated negative electrode sheet and separator prepared above are stacked in order so that the separator is between the positive and negative electrode sheets, and then wound to obtain a bare battery cell, which is then placed in an aluminum-plastic film soft package, and after drying, the electrolyte is injected, and a soft-pack sodium-ion battery is obtained after vacuum packaging, standing, forming, shaping and other processes.

[0097] Example 2 to Example 13

[0098] The preparation methods of Examples 2 to 13 are substantially the same as that of Example 1, and the differences are detailed in Table 1.

[0099] Table 1

[0100]

[0101] Embodiment 14

[0102] The preparation method of Example 14 is substantially the same as that of Example 3, except that:

[0103] During the formation of the ceramic coating, the mass ratio of the ceramic material alumina to the aqueous binder SBR is 9:1.

[0104] Embodiment 15

[0105] The preparation method of Example 15 is substantially the same as that of Example 3, except that:

[0106] During the formation of the ceramic coating, the mass ratio of the ceramic material alumina to the aqueous binder SBR is 7:3.

[0107] Example 16

[0108] The preparation method of Example 16 is substantially the same as that of Example 3, except that:

[0109] The PVDF-HFP organic adhesive layer is replaced by a PMMA organic adhesive layer.

[0110] Embodiment 17

[0111] The preparation method of Example 17 is substantially the same as that of Example 3, except that:

[0112] During the formation of the negative electrode coating, the mass ratio of the conductive carbon black SP to the binder PAA was 9:1.

[0113] Embodiment 18

[0114] The preparation method of Example 18 is substantially the same as that of Example 3, except that:

[0115] During the formation of the negative electrode coating, the mass ratio of the conductive carbon black SP to the binder PAA is 7:3.

[0116] Comparative Example 1

[0117] The preparation method of this comparative example is basically the same as that of Example 3, except that:

[0118] In this comparative example, no diaphragm coating was provided.

[0119] Comparative Example 2

[0120] The preparation method of this comparative example is basically the same as that of Example 3, except that:

[0121] In the diaphragm coating of this comparative example, only a ceramic coating (the thickness of the ceramic coating is 14.4 μm) is provided, and no organic glue layer is provided.

[0122] The 100-cycle cycle capacity retention rate and the full-charge cell expansion rate of Examples 1 to 18 and Comparative Examples 1 to 2 were tested respectively, and the results are shown in Table 2.

[0123] Cycle capacity retention test:

[0124] The cell is cycled 100 times at room temperature and 1C, and the capacity retention rate = discharge capacity (100 th ) / discharge capacity(1 st )

[0125] The battery was placed on a charge and discharge instrument (Nebula Charge and Discharge Test System-BAT-NEEFLCT-05300-V010) for charge and discharge cycle testing. The test temperature was 25°C, the cycle rate was 1C (i.e., both the charge rate and the discharge rate were 1C), the charge and discharge voltage range was 1.5V to 3.5V, and the capacity retention rate after 100 cycles was calculated. Among them, the capacity retention rate calculation formula for the 25°C cycle is: capacity retention rate after the nth cycle = (discharge capacity after the nth cycle / discharge capacity of the first cycle) × 100%.

[0126] Fully charged cell expansion rate test:

[0127] The battery was placed on the Blue Electric system for a full charge test at a test temperature of 25°C and a charge rate of 1C. After the cell was fully charged, a micrometer was used to test the thickness, and the expansion rate = (thickness after full charge - initial thickness) / initial thickness.

[0128] Table 2

[0129]

[0130]

[0131] It can be seen from Table 2 that compared with Comparative Example 1, the cycle capacity retention rates of Examples 1 to 18 are significantly improved, and the fully charged cell expansion rates of Examples 1 to 18 are significantly reduced. It can be seen that by arranging a diaphragm coating on both sides of the diaphragm substrate, the negative electrode coating, the diaphragm coatings on both sides and the diaphragm substrate can jointly form a space, which can be used to accommodate the sodium metal released by the positive electrode sheet, thereby effectively avoiding the internal stress accumulation of the battery cell caused by the volume change of the active metal on the negative electrode side. At the same time, the diaphragm and the negative electrode sheet can also be effectively formed into an integrated structure, which improves the strength of the negative electrode sheet, thereby effectively avoiding the problems of low battery processing efficiency and decreased flatness of the current collector caused by weak strength and easy wrinkling of the negative electrode sheet, problems affecting the nucleation of the active metal on the negative electrode side, and the cycle life attenuation of the battery and the generation of dendrites. In summary, Examples 1 to 18 effectively improve the cycle capacity retention rate of the battery and effectively reduce the fully charged cell expansion rate of the battery by arranging a diaphragm coating on both sides of the diaphragm substrate.

[0132] It can also be seen from Table 2 that compared with Comparative Example 2, the cycle capacity retention rate of Example 3 is improved, and the expansion rate of the fully charged cell of Example 3 is reduced. It can be seen that the organic glue layer of Example 3 can effectively realize the formation of an integrated structure between the separator and the negative electrode sheet, and improve the strength of the negative electrode sheet. Therefore, compared with Comparative Example 2, the cycle capacity retention rate of Example 3 is improved. In Comparative Example 2, since no organic glue layer is provided, the separator and the negative electrode sheet cannot form an integrated structure, and the negative electrode is severely damaged / wrinkled during the processing of the electrode sheet / battery cell, so its cycle capacity retention rate is relatively low.

[0133] It can also be seen from Table 2 that compared with Examples 6 and 7, the cycle capacity retention rate of Examples 1 to 5 is improved, and the full charge core expansion rate of Examples 1 to 5 is further reduced. It can be seen that when the thickness H of the diaphragm coating satisfies: H ≥ Q 正极 / (Q 活性金属 ·S 正极 )·(1±0.3), the cycle capacity retention rate and full charge cell expansion rate of the battery are excellent. Further, when the thickness H of the separator coating satisfies: H≥Q 正极 / (Q 活性金属 ·S 正极 ), the battery's cycle capacity retention rate and full-charge cell expansion rate are even better.

[0134] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0135] Although the embodiments of the present application have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations on the present application. Ordinary technicians in this field can change, modify, replace and modify the above embodiments within the scope of the present application.

Claims

1. A battery, characterized in that: include: A positive electrode sheet and a separator-negative electrode assembly, wherein the separator-negative electrode assembly comprises a negative electrode sheet and a separator, wherein the separator is arranged between the positive electrode sheet and the negative electrode sheet, and wherein the separator comprises a separator substrate and a separator coating, wherein the separator coating is arranged on a portion of the surface of the separator substrate close to the negative electrode sheet, and the separator coating is arranged on both sides of the separator substrate in a width direction beyond the positive electrode sheet; The negative electrode sheet includes a negative electrode current collector and a negative electrode coating, wherein the negative electrode coating is arranged on at least a portion of the surface of the negative electrode current collector close to the diaphragm, and the two ends of the negative electrode coating along the width direction are respectively bonded to at least a portion of the diaphragm coating on both sides of the diaphragm substrate along the width direction to form a bonding area, and the bonding area is formed by hot pressing the negative electrode sheet and the diaphragm after stacking, and the negative electrode coating, the diaphragm coating on both sides and the diaphragm substrate together form a space, and the space is used to accommodate the metal formed by the active ions released by the positive electrode sheet deposited on the negative electrode side.

2. The battery according to claim 1, characterized in that The positive electrode sheet includes a positive electrode current collector and a positive electrode active material, and the thickness H of the separator coating satisfies: H≥Q 正极 / (Q 活性金属 ·S 正极 )·(1±0.3), where Q 正极 represents the capacity released by the positive electrode active material, Q 活性金属 represents the volume gram capacity of the active metal of the positive electrode active material, S 正极 Represents the area of ​​the positive electrode sheet.

3. The battery according to claim 2, characterized in that The active metal of the positive electrode active material includes at least one of sodium and lithium.

4. The battery according to claim 2, characterized in that The diaphragm coating includes a ceramic coating and an organic glue layer. The ceramic coating is arranged on a portion of the surface of the diaphragm substrate close to the negative electrode sheet, and the ceramic coating is arranged on both sides of the diaphragm substrate beyond the positive electrode sheet in the width direction. The organic glue layer is arranged on at least a portion of the surface of the ceramic coating away from the diaphragm substrate.

5. The battery according to claim 4, characterized in that The ceramic coating comprises a ceramic material and a first aqueous binder, and the mass ratio of the ceramic material to the first aqueous binder is 9 / 1 to 7 / 3; And / or, the organic glue layer includes at least one of polyvinylidene fluoride-propylene fluoride and polymethyl methacrylate; And / or, the thickness of the organic glue layer is 0.5 μm to 2 μm, and the thickness of the ceramic coating is equal to the difference between the thickness H of the diaphragm coating and the thickness of the organic glue layer.

6. The battery according to claim 5, characterized in that The ceramic material includes at least one of alumina and boehmite; And / or, the first aqueous binder includes at least one of styrene-butadiene rubber, carboxymethyl cellulose and polyacrylic acid.

7. The battery according to any one of claims 1 to 6, characterized in that The width of the negative electrode coating bonded to the separator coating on one side is 1 mm to 10 mm.

8. The battery according to any one of claims 1 to 6, characterized in that The negative electrode coating comprises a conductive carbon material and a second aqueous binder, and the mass ratio of the conductive carbon material to the second aqueous binder is 9 / 1 to 7 / 3; And / or, the thickness of the negative electrode coating is 1 μm to 2 μm.

9. The battery according to claim 8, characterized in that The conductive carbon material includes at least one of conductive carbon black, carbon nanotubes, graphene, and carbon fiber; And / or, the second aqueous binder includes at least one of styrene-butadiene rubber, carboxymethyl cellulose and polyacrylic acid.

10. A method for preparing a battery as claimed in any one of claims 1 to 9, characterized in that: include: forming a negative electrode coating on at least a portion of the surface of the negative electrode current collector to obtain a negative electrode sheet; Forming membrane coatings on both sides of the membrane substrate along the width direction to obtain a membrane; The negative electrode sheet and the separator are stacked and hot pressed so that both ends of the negative electrode coating along the width direction are at least partially bonded to the separator coating on both sides to form a separator-negative electrode assembly, and the negative electrode coating, the separator coating on both sides and the separator substrate together form a space.

11. The method according to claim 10, characterized in that The temperature of the hot pressing is 60° C. to 80° C., the pressure of the hot pressing is 1 MPa to 2 MPa, and the time of the hot pressing is 1 min to 5 min.

12. An energy storage device, characterized in that: A battery comprising the battery according to any one of claims 1 to 9 or a battery obtained by the method according to claim 10 or 11.

13. An electricity system, characterized in that: include: Electrical equipment, and The energy storage device as claimed in claim 12, wherein the energy storage device supplies power to the electrical equipment.